The History of Arabic Language Teaching Development - Lubis, Muhammad Ajiji; Wahyudi, Hakmi; Utami, Diah Ira (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
The development of Arabic language teaching has undergone a significant transformation over time. From the beginning of its spread which is closely related to the development of Islam, Arabic has become the main medium in conveying religious teachings and knowledge. The teaching of this language has undergone various changes in methods, ranging from traditional approaches to modern approaches that are more interactive. The purpose of this study is to understand the origins and heritage of the Arabic language, identify changes in teaching approaches, assess the effectiveness of teaching methods, encourage teaching innovation and improvement, and preserve and develop cultural heritage. The research method used is library research. Primary data sources include classical Arabic texts, traditional educational manuscripts, and educational institution documents. documents of educational institutions. Secondary data sources include history books, academic journals, theses and dissertations, and reports from conferences and seminars. The results show that the history of the development of Arabic language teaching has gone through an interesting evolution throughout the centuries. In the early days, Arabic language teaching was centered in madrasas and universities that developed classical text- based methods and systematic grammar. Over time, Arabic teaching methods underwent a significant transformation with the development of technology and innovative educational approaches.